INDOCTRINATION AS THE TOOL OF RUSSIA'S HYBRID WAR - Сафін, О. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
Psychological peculiarities of the mechanism of indoctrination as a tool of modern hybrid war of Russia against Ukraine and its own people have been revealed. The principal social-psychological indicators of degradation of modern Russian ideology and forms of its realization in destructive forms of internal and external interaction have been considered. Key words: indoctrination, hybrid warfare, indicators of degradation, destructive forms.